2008
DOI: 10.1002/hipo.20515
|View full text |Cite
|
Sign up to set email alerts
|

Category‐specificity in the human medial temporal lobe cortex

Abstract: The medial temporal lobe cortex (MTLC) occupies a pivotal position at the interface between neocortical association areas and the hippocampus. It has been suggested that the MTLC contains functionally distinct regions, with perirhinal cortex (PRc) preferentially supporting object processing and posterior parahippocampal cortex (PHc) preferentially supporting encoding of spatial information. Measuring differential BOLD responsiveness to objects, scenes and other stimulus categories, we find a double dissociatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
106
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 55 publications
20
106
2
Order By: Relevance
“…For example, fMRI studies have shown content specialization within the MTL cortex that is predictive of subsequent memory. Specifically, consistent with their differing connectivity with other cortical areas (Suzuki 2009), activity in the parahippocampal cortex at encoding has been shown to predict later memory for scenes, while activity in the perirhinal cortex at encoding predicts later memory for faces, objects (Litman et al 2009;Preston et al 2010;Staresina and Davachi 2010;Staresina et al 2011), and their associations (Staresina and Davachi 2008;Watson et al 2012). Convergent evidence suggests that such functional differentiation along the anteriorposterior axis of the MTL cortex is best understood as a continuous gradient; for example, Liang and colleagues (2013) showed that face/ object and scene representations are coded to differing degrees across the MTL cortex, with the greatest specialization for scene memory in the posterior parahippocampal region and greatest specialization for face/object processing in the perirhinal cortex (see also Lee et al 2008;Barense et al 2010).…”
Section: Testing Theories Of Mtl Functional Differentiationmentioning
confidence: 82%
“…For example, fMRI studies have shown content specialization within the MTL cortex that is predictive of subsequent memory. Specifically, consistent with their differing connectivity with other cortical areas (Suzuki 2009), activity in the parahippocampal cortex at encoding has been shown to predict later memory for scenes, while activity in the perirhinal cortex at encoding predicts later memory for faces, objects (Litman et al 2009;Preston et al 2010;Staresina and Davachi 2010;Staresina et al 2011), and their associations (Staresina and Davachi 2008;Watson et al 2012). Convergent evidence suggests that such functional differentiation along the anteriorposterior axis of the MTL cortex is best understood as a continuous gradient; for example, Liang and colleagues (2013) showed that face/ object and scene representations are coded to differing degrees across the MTL cortex, with the greatest specialization for scene memory in the posterior parahippocampal region and greatest specialization for face/object processing in the perirhinal cortex (see also Lee et al 2008;Barense et al 2010).…”
Section: Testing Theories Of Mtl Functional Differentiationmentioning
confidence: 82%
“…However, this does not rule out the possibility that PRC and PHC may still interact, e.g., via the dense projections from PHC to PRC (but less vice versa) (Suzuki and Amaral, 1994b). Furthermore, material sensitivity along the anteriorposterior MTL axis might be gradual rather than categorical (Litman et al, 2009). …”
Section: Perirhinal and Parahippocampal Cortexmentioning
confidence: 95%
“…3, 4), which may have several reasons. First, we did not directly present images from different categories (Litman et al, 2009) but used an abstract cue. Second, neighboring MTL regions may inhibit each other through interconnections (Suzuki and Amaral, 1994b;Burwell, 2000;Lavenex and Amaral, 2000), and higher PHC-MEC activation for scenes after distraction might thus lead to PRC-LEC deactivation, and vice versa.…”
Section: Domain Sensitivity and The Role Of Distractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, neuroimaging studies using stimuli with strong and weak contextual associations have identified the components and basic properties of the network that mediates context-based associations; studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have reported a core set of regions (Fig. 1A) that are activated by contextual associations: the parahippocampal cortex (PHC), the retrosplenial complex (RSC), and in some cases, the medial prefrontal cortex (MPFC).…”
mentioning
confidence: 99%